AN ANALYSIS OF SPEECH ACTS IN CLASSROOM INTERACTION BETWEEN TEACHERS AND STUDENTS: A STRUCTURED PRAGMATIC REVIEW AND PEDAGOGICAL SYNTHESIS - Rita Oktavia; Khairil Hadi; Nattapong Srisuk (SENSEI RESEARCH CENTER, 2026)
In the classroom the teacher and the students always talk, and every utterance actually has a function, for example to ask, to command, to praise, or to explain. This is called speech act. This article analyzes speech acts in classroom interaction between teachers and students. The method used is literature review from journals about pragmatics and classroom discourse. The result shows that the teacher usually uses directive, representative, and expressive speech acts, while the students mostly only answer the question of the teacher. If the teacher gives more chance, the students can also ask and give opinion. Therefore the teacher must be aware of the speech acts that are used because it influences the participation of the students in the classroom.